Analisis Spasial Respon Situs Berdasarkan Vs30 USGS, Estimasi Amplifikasi dan Periode Dominan di Seram Bagian Timur - Rimawanto Gultom; Sarinah Pakpahan; Nasya Syahnur Pattimura; Ratih C F Ratumanan; Sri Indriati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study focuses on Seram Bagian Timur, an area known for its complex geological setting and active tectonic. Recent seismic events, including the 26 September 2019 Ambon earthquake (Mw 6.5) and the 22 June 2025 earthquake near Bula (Mw 5.0), indicate the presence of active fault systems and heterogeneous subsurface conditions. These conditions govern how seismic waves are modified at the ground surface particularly variation in subsurface material properties. This effect is represented by the amplification factor, which estimated using the empirical relationship proposed by Fujimoto and Midorikawa. The objective of this study is to examine the spatial variability of site response using Vs30 data from USGS, along with amplification factors and dominant periods. The analysis is based on 6,550 grid points with a spatial resolution of approximately 930 m, supported by regional geological information. Data processing involved extraction, interpolation, and mapping, while amplification and dominant period were estimated using empirical approach The results indicate that Vs30 values range from 180 to 900 m/s (site classes BC–E), with lower values concentrated in coastal and eastern areas, and higher values predominantly found in the western part of the study area. Amplification factors vary between 0.77 and 2.79, generally falling within low to moderate categories. Meanwhile, dominant periods range from 0.133 to 0.667 seconds, representing soil types from hard to very soft conditions. Overall, the three parameters show a consistent pattern, where lower Vs30 values tend to correspond to higher amplification and longer dominant periods, reflecting less consolidated subsurface materials.